The Fourfold Gospel : A Theological Reading of the New Testament Portraits of Jesus - Watson, Francis, 1956- (Grand Rapids, MI : Baker Academic, 2016)
This groundbreaking approach to the study of the fourfold gospel offers a challenging alternative to prevailing assumptions about the creation of the gospels and their portraits of Jesus. How and why does it matter that we have these four gospels? Why were they placed alongside one another as four parallel yet diverse retellings of the same story? Francis Watson, widely regarded as one of the foremost New Testament scholars of our time, explains that the four gospels were chosen to give a portrait of Jesus. He explores the significance of the fourfold gospel's plural form for those who constructed it and for later Christian communities, showing that in its plurality it bears definitive witness to what God has done in Jesus Christ. Watson focuses on reading the gospels as a group rather than in isolation and explains that the fourfold gospel is greater than, and other than, the sum of its individual parts. Interweaving historical, exegetical, and theological perspectives, this book is accessibly written for students and pastors but is also of interest to professors and scholars.
Prolegomena: The making of a fourfold gospel -- Part 1. Perspectives -- The first gospel: Jesus the Jew -- The second gospel: preparing the way -- The third gospel: Magnificat -- The fourth gospel: seeing God -- Part 2. Convergences -- Four gospels, one book -- The city and the garden -- Christus victor -- The truth of the gospel.
Includes bibliographical references and index.
Keywords: Jesus Christ; Bible. -- Criticism, interpretation, etc; Bible. -- Hermeneutics; Bible. -- Theology; Gospel Hermeneutics; Criticism, interpretation, etc